ERROR ANALYSIS OF JAPANESE PASSIVE SENTENCE COMPREHENSION IN WRITTEN VARIANT AMONG STUDENTS OF JAPANESE LANGUAGE AND CULTURE STUDY PROGRAM AT UNSADA - Andi Irma Sarjani; Juariah, Aisyah Rasuna Syamsi (Adisam Publisher, 2024)
This study discusses the